2016
DOI: 10.1667/rr14357.1
|View full text |Cite
|
Sign up to set email alerts
|

Late Effects of Total-Body Gamma Irradiation on Cardiac Structure and Function in Male Rhesus Macaques

Abstract: Heart disease is an increasingly recognized, serious late effect of radiation exposure, most notably among breast cancer and Hodgkin’s disease survivors, as well as the Hiroshima and Nagasaki atomic bomb survivors. The purpose of this study was to evaluate the late effects of total-body irradiation (TBI) on cardiac morphology, function and selected circulating biomarkers in a well-established nonhuman primate model. For this study we used male rhesus macaques that were exposed to a single total-body dose of io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…Heart disease is an increasingly recognized, serious late effect of radiation exposure. A recent study conducted in NHPs demonstrated that single total-body doses of 6.5 – 8.4 Gy produced long-term effects including a high incidence of myocardial fibrosis, reduced left ventricular diameter, and elevated systemic inflammation [54]. Also, the kidney has been shown to be one of the most radiosensitive late-responding organs in humans with chronic renal injuries occurring after single doses as low as 4–6 Gy.…”
Section: Suitability Of Nhps As Animals Models For Studying Radiatmentioning
confidence: 99%
“…Heart disease is an increasingly recognized, serious late effect of radiation exposure. A recent study conducted in NHPs demonstrated that single total-body doses of 6.5 – 8.4 Gy produced long-term effects including a high incidence of myocardial fibrosis, reduced left ventricular diameter, and elevated systemic inflammation [54]. Also, the kidney has been shown to be one of the most radiosensitive late-responding organs in humans with chronic renal injuries occurring after single doses as low as 4–6 Gy.…”
Section: Suitability Of Nhps As Animals Models For Studying Radiatmentioning
confidence: 99%
“…We screened serum samples for a panel of markers of microbial translocation, as myeloablative conditioning can trigger gut damage and microbial translocation (28)(29)(30) (Figure 7, A-C). Zonulin, a marker of gut epithelium tight junctions and gut integrity, was significantly increased during transplant recovery, and remained higher following cART withdrawal (P = 0.0159 at post-transplant time point I [post-Tx I], P = 0.031 at post-Tx II, P = 0.028 at cART withdrawal (ART WD in figure), and P = 0.057 at necropsy) ( Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…Other large animals such as non-human primates and pigs have been used by a few groups to study RIHD [146][147][148], but these are uncommon given the high cost and low throughput nature of large animal models.…”
Section: Non-humanmentioning
confidence: 99%